Archaeology in a scrapyard, or how a monument ceases to be a monument - Florek, Marek; Kokowski, Andrzej (the Authors, 2020)
Amateur searches for archaeological artefacts, most frequently with the use of metal detectors, are generally aimed at building up private collections. They have also become a source of income in the illegal trade in artefacts. Collecting ancient artefacts as recyclable metal is a new phenomenon. At the scrapyard in Milczany, Sandomierz district, several kilograms of such scrap were found, among which two fibulae from the Roman period, Almgren 67 and 43, were recognised. They are valuable in the research into the history of the Przeworsk Culture. The authors also note the widespread practice of collecting striped flint, used by modern jewellers, which has resulted in the devastation of several sites which were relics of ancient mines of this material. The authors consider the scientific value of the recovered artefacts, which often cannot be localised precisely. They call for the unceasing promotion of the value of archaeological artefacts and indicate its effectiveness in the Hrubieszow Basin.
Keywords: Protection of archaeological cultural heritage; metal detectors; ancient materials; modern materials; Roman period; fibulae